Co-optimization of multi-energy system operation, district heating/cooling network and thermal comfort management for buildings. (15th November 2021) - Ghilardi, Lavinia Marina Paola; Castelli, Alessandro Francesco; Moretti, Luca; Morini, Mirko; Martelli, Emanuele
Highlights: MILP model for co-optimization of operation of MES, DHN and thermal comfort. Heat capacity of buildings and DHN can be exploited as additional storages. Weekly management strategies for overall integrated system are optimized. Tests on 16 case studies show energy cost savings in the range 5–80%. Abstract: The ongoing decarbonization of the energy sector spurs the employment of distributed generation and efficient load control approaches (demand side management). This work tackles the optimal operation of a Multi Energy System and thermal comfort management for buildings with an integrated approach. The dynamic thermal energy balance of the buildings is included in the Mixed Integer Linear Programming scheduling problem to exploit the heat capacity of buildings and increase the operational flexibility of the generators. The method is firstly applied to a single building served by different energy systems, comprising renewable energy sources, cogeneration units and heat pumps. Then, the methodology is further extended by integrating in the formulation the model of the district heating/cooling network. This method is tested in a group of 12 buildings of the Campus of University of Parma, featuring different thermal properties. By enabling a variation within ± 2 °C around the indoor temperature setpoint and by optimizing water delivery temperature, it is possible to achieve savings on operating costs over the baseline up to 80%. Results show that the load shift capability of buildings plays a major role when thermal demand mismatches renewable energy availability or low electricity price periods. Moreover, district heating network can be exploited as an additional short-term heat storage by varying water delivery temperature profile.